2013
DOI: 10.1098/rstb.2012.0300
|View full text |Cite
|
Sign up to set email alerts
|

State and evolution of the African rainforests between 1990 and 2010

Abstract: This paper presents a map of Africa's rainforests for 2005. Derived from moderate resolution imaging spectroradiometer data at a spatial resolution of 250 m and with an overall accuracy of 84%, this map provides new levels of spatial and thematic detail. The map is accompanied by measurements of deforestation between 1990, 2000 and 2010 for West Africa, Central Africa and Madagascar derived from a systematic sample of Landsat images—imagery from equivalent platforms is used to fill gaps in the Landsat record. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
160
2
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(177 citation statements)
references
References 38 publications
4
160
2
3
Order By: Relevance
“…High rates of deforestation in Africa's rainforests in the Congo Basin and Madagascar were reported between 1990 and 2010 by Mayaux et al (2014). This pattern was not observed from the NDVI study here, probably because of the saturation of NDVI in dense forest (Atkinson et al, 2011).…”
Section: A Conceptual Model -Link With Previous Studiescontrasting
confidence: 61%
“…High rates of deforestation in Africa's rainforests in the Congo Basin and Madagascar were reported between 1990 and 2010 by Mayaux et al (2014). This pattern was not observed from the NDVI study here, probably because of the saturation of NDVI in dense forest (Atkinson et al, 2011).…”
Section: A Conceptual Model -Link With Previous Studiescontrasting
confidence: 61%
“…Between 1990 and 2000 Cameroon's estimated annual net deforestation rate was 0.08% (15,272 ha), and decreased to 0.03% (5727 ha) between 2000 and 2005. Conversely, the annual net forest degradation rate was 0.06% (11,454 ha) between 1990 and 2000 and rose to 0.07% (13,363 ha) between 2000 and 2005 in the category "dense forest" (Ernst et al 2012). Deforestation and forest degradation rates in the Congo Basin are generally lower than in other regions (Mayaux et al 2013), and Rudel (2013) argues that state income in the Basin, including tax revenues from oil and mineral industries, could explain these lower deforestation and degradation rates because of increased imports and migration dynamics. Although some scholars argue that "well-controlled" timber exploitation has seemingly little direct influence on forest-cover reduction (Mayaux et al 2013), it would be necessary, especially from a political economy perspective, to investigate current timber exploitation schemes and the implications for emissions.…”
Section: Theory and Backgroundmentioning
confidence: 99%
“…The most rapid rates of deforestation between 2000 and 2012, in analyses of the LANDSAT data, occurred in the dry forest regions of Paraguay and Argentina, where a wave of large-scale, industrialized agricultural expansion occurred [10,37]. Similarly, very detailed remote sensing analyses of deforestation in the wet forests of the Congo River basin between 1990 and 2010 demonstrated that small-scale cultivators drove much of the deforestation by opening up new fields adjacent to old fields close to the villages where they resided [38]. These admittedly large exceptions aside, the binary of artisanal production in dry tropical forests and industrial production in wet tropical forests finds some empirical support in this analysis, and could serve some useful heuristic purposes in future policy making and research on tropical deforestation.…”
Section: Discussionmentioning
confidence: 99%